Experimental Substantiation of New Presentation Form of Cholera Diagnostic Sera - A. V. Komissarov; M. V. Ovchinnikova; S. A. Badarin; D. N. Bibikov; N. V. Sinitsyna; N. I. Kostyleva; I. A. Plotnikov (Проблемы особо опасных инфекций, 2017)
Objective of the study is experimental substantiation of possibility to produce new presentation form of cholera diagnostic sera – lyophilizate in bottles. Materials and methods. Cholera diagnostic sera. Liophylization was performed in Martin Christ Epsilon 2-6D. Residual moisture of dry sera was determined using humidity meter Sartorius MA 150. Solubility of experimental samples was assessed visually. pH was evaluated by potentiometry with the help of PK SevenExcellence-475 Mettler Toledo device, measuring pH/ORP/Ion content/conductivity/concentration. Specific activity and specificity was analyzed through expanded agglutination reaction, using relevant control strains of cholera vibrio. Results and conclusions. Experimentally justified is the possibility to lyophilize cholera diagnostic sera in flasks. Specified are the optimum parameters of lyophilization. It is determined that lyophilization does not result in deterioration of properties, as judging by the quality indicators they meet the requirements of regulatory documentation. Using accelerated aging test, it is demonstrated that the new presentation form of cholera diagnostic sera – lyophilizate in flasks – maintains their specific activity within five years term (the set out shelf life), which fully conform to normative standards.